The Influence of Organizational Culture and Competency on Employee Engagement and Its Impact on Managerial Performance - Annisa Nur Luthfiana Fajrin; Rizka Amaliah; Kartono Kartono (Universitas KH. Abdul Chalim Mojokerto, 2025)
In today's rapidly evolving port industry, there is an increasing need for companies to enhance their managerial performance by improving organizational culture and developing the competencies of their team members. This study examines how organizational culture and team member competencies influence employee engagement and, consequently, affect managerial performance at PT Pelindo Cirebon. A quantitative research approach was used, employing a saturated sampling technique that included all 58 employees of the company as respondents. Data analysis was performed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings indicate that both organizational culture and competencies have a positive and significant impact on employee engagement. Moreover, employee engagement has a positive and significant effect on managerial performance.